2017
DOI: 10.1080/10717544.2017.1346002
|View full text |Cite
|
Sign up to set email alerts
|

Borneol, a novel agent that improves central nervous system drug delivery by enhancing blood–brain barrier permeability

Abstract: The clinical application of central nervous system (CNS) drugs is limited by their poor bioavailability due to the blood-brain barrier (BBB). Borneol is a naturally occurring compound in a class of 'orificeopening' agents often used for resuscitative purposes in traditional Chinese medicine. A growing body of evidence confirms that the 'orifice-opening' effect of borneol is principally derived from opening the BBB. Borneol is therefore believed to be an effective adjuvant that can improve drug delivery to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 55 publications
(75 reference statements)
1
74
0
2
Order By: Relevance
“…In the current studies, we thus conducted both in vitro and in vivo experiments delay gastric empty and prolong bowel transit time. 54,55 We will conduct clinical studies to further investigate whether PB2 assisted with…”
Section: Discussionmentioning
confidence: 99%
“…In the current studies, we thus conducted both in vitro and in vivo experiments delay gastric empty and prolong bowel transit time. 54,55 We will conduct clinical studies to further investigate whether PB2 assisted with…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticles significantly increased ITC uptake by the bEnd.3 cells (a mouse brain cell line) and promoted~2-fold higher brain uptake in mice than ITC conventional formulation [115]. Borneol is a highly lipid-soluble bicyclic monoterpene that can facilitate penetration of drugs in the brain due to BBB opening [116]. Another study used a 29-amino-acid peptide derived from rabies virus glycoprotein (RVG29) conjugated with albumin nanoparticles as carrier for ITC (RVG29-ITC-NP), and demonstrated a significant drug accumulation in the brain compared to albumin nanoparticles without RVG29 and a cyclodextrin formulation of ITC [117].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…Cao et al [154] demonstrated that borneol may be a novel therapeutic agent for fear and anxiety disorders. Wu et al [155] demonstrated that borneol increased blood-brain barrier permeability; related to increased ICAM-1 expression, thus becoming a promising candidate for treatment of brain tumors and infections, as well as chronic disorders in the central nervous system [155,156]. In an experimental model of permanent cerebral ischemia, borneol reduced the size of ischemia by decreasing expression of nitric oxide synthase and TNF-α in a dose-dependent manner [157].…”
Section: Borneolmentioning
confidence: 99%